Sustainable Environmental Planning in Pampa Biome: A Case Study, São Francisco de Assis –RS, Brazil (ARQUISUR Revista, 2014)
The Pampa Biome, listed by UNESCO (2008) extends from southern Brazil to Uruguay and neighboring Argentina. São Francisco de Assis, a city of the south of Rio Grande do Sul, has in its territory an important area of environmental fragility: a buffer zone between the Mata Atlântica and the Bioma Pampa. At the headquarters city of São Francisco de Assis did an unusual case: a bunch of apes made its central square of its habitat. Adopted, the urban population took on the identity "Querência do Bugio." This fact led the Urban Planners to wonder as to why these animals did not stay in the woods, their place of origin –deforestation environmental degradation. Around the urban site, over three water sources Municipal Park was created Bugio and extensions of these more distant sources to the woods in rural areas, ecological corridors. Proposals for land use determined guidelines for reforestation, restoration of riparian forests and numerous gullies that caused soil degradation and a growing process of sandy desertification. The presence of monkeys in the square triggered a process of recovery and preservation of environmental awareness in the Pampa biome and local identity.